Predation response of vibrio fischeri biofilms to bacterivorus protists - Chavez-Dozal, Alba (2015)
Vibrio fischeri proliferates in a sessile, stable community known as a biofilm, which is one alternative survival strategy of its life cycle. Although this survival strategy provides adequate protection from abiotic factors, marine biofilms are still susceptible to grazing by bacteria-consuming protozoa. Subsequently, grazing pressure can be controlled by certain defense mechanisms that confer higher biofilm antipredator fitness. In the present work, we hypothesized that V. fischeri exhibits an antipredator fitness behavior while forming biofilms. Different predators representing commonly found species in aquatic populations were examined, including the flagellates Rhynchomonas nasuta and Neobodo designis (early biofilm feeders) and the ciliate Tetrahymena pyriformis (late biofilm grazer). V. fischeri biofilms included isolates from both seawater and squid hosts (Euprymna and Sepiola species). Our results demonstrate inhibition of predation by biofilms, specifically, isolates from seawater. Additionally, antiprotozoan behavior was observed to be higher in late biofilms, particularly toward the ciliate T. pyriformis; however, inhibitory effects were found to be widespread among all isolates tested. These results provide an alternative explanation for the adaptive advantage and persistence of V. fischeri biofilms and provide an important contribution to the understanding of defensive mechanisms that exist in the out-of-host environment.